2020
DOI: 10.1002/jcph.1621
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, Excretion, and Pharmacokinetics of Lorlatinib (PF‐06463922) and Evaluation of the Impact of Radiolabel Position and Other Factors on Comparability of Data Across 2 ADME Studies

Abstract: While an initial clinical absorption, distribution, metabolism, and excretion (ADME) study (Study 1; N = 6) with 100 mg/100 µCi [14C]lorlatinib, radiolabeled on the carbonyl carbon, confirmed that the primary metabolic pathways for lorlatinib are oxidation (N‐demethylation, N‐oxidation) and N‐glucuronidation, it also revealed an unanticipated, intramolecular cleavage metabolic pathway of lorlatinib, yielding a major circulating benzoic acid metabolite (M8), and an unlabeled pyrido‐pyrazole substructure. Concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In vitro studies indicated that lorlatinib is a time-dependent inhibitor, as well as an inducer, of CYP3A via PXR activation [ 6 ]; thus, it was unclear if the net effect on CYP3A would be induction or inhibition. In the phase I midazolam substudy, lorlatinib was demonstrated to be a net moderate inducer of CYP3A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies indicated that lorlatinib is a time-dependent inhibitor, as well as an inducer, of CYP3A via PXR activation [ 6 ]; thus, it was unclear if the net effect on CYP3A would be induction or inhibition. In the phase I midazolam substudy, lorlatinib was demonstrated to be a net moderate inducer of CYP3A.…”
Section: Discussionmentioning
confidence: 99%
“…Two absorption, metabolism, and excretion studies conducted in healthy participants have shown that lorlatinib is primarily eliminated via metabolism, with little renal excretion (< 5% of administered dose recovered in urine) [ 6 ]. The most abundant circulating human metabolite of lorlatinib is PF-06895751, which is pharmacologically inactive and is generated by the oxidative cleavage of the lorlatinib amide and aromatic ether bonds [ 6 ]. Lorlatinib is metabolized primarily by cytochrome P450 (CYP) 3A and UGT1A4, and to a lesser extent by CYP2C8, CYP2C19, CYP3A5, and UGT1A3 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma and urine samples were analyzed for lorlatinib concentrations using validated, sensitive, and specific highperformance liquid chromatography-tandem mass spectrometric methods (HPLC-MS/MS) as previously described [9][10][11]. Plasma samples were analyzed for PF-06895751 concentrations by a validated LC-MS/MS method.…”
Section: Pharmacokinetic Assessmentsmentioning
confidence: 99%
“…On the basis of findings from nonclinical in vitro studies and in vivo metabolic profiling, it was determined that extensive metabolism of lorlatinib occurred via oxidation and conjugation [ 6 ]. In two human absorption, distribution, metabolism, and excretion (ADME) studies, also called mass balance studies, unchanged lorlatinib accounted for < 2% of the dose in urine, indicating minimal urinary excretion of the parent drug [ 6 ]. Therefore, renal impairment would not be expected to have a major effect on lorlatinib pharmacokinetics or safety.…”
Section: Introductionmentioning
confidence: 99%
“…This is also consistent with a similar reduction in M8 AUC inf noted in the prior drug interaction study with rifampin [ 6 ]. The absorption, distribution, metabolism, and excretion properties of lorlatinib have been characterized separately [ 10 ].…”
Section: Discussionmentioning
confidence: 99%